A preliminary study on the use of Epithets in Kenyah Long Wat - Lendik Edmond, Lisbeth Sinan; Chan, Mei Yuit (Global Council on Anthropological Linguistics, 2021)
One’s social status has long been the point of reference in the effort to address the individual. As observed in the Kenyah Long Wat community, whenever one parent passes away, the whole family will be given epithets that signify the death. Likewise, the gender of the first newborn in a family will influence the epithets given to the parents. This practice indicates how a social event influences a language, and in particular, the Kenyah Long Wat, which is categorised as an endangered language. Although the creation and use of epithets in indexing life events is not customary to this particular language alone, the types and varieties of linguistic forms used in different language communities may well provide a lens through which the social practices of an indigenous community can be appreciated. Furthermore, describing the use of epithets becomes an important aspect of documenting and describing an endangered language such as the Kenyah Long Wat. The indigenous epithet is fast disappearing among the younger members of the Long Wat community, as these younger generations have become prone to using mainstream Malay and English terms of address.